Exploring the Combined Impact of Environmental Policy Stringency and Institutional Quality on Sustainable Energy: Evidence from Top 14 Green Economies - Akhtar, Muhammad Sohail; Nazeer, Aneeqa; Iram, Maria; Zameer, Sahrish (Pakistan Journal of Humanities and Social Sciences, 2024)
The growing concern for a green economy increases the demand for sustainable energy. Previous studies massively concentrate on solutions to achieve the target of sustainable energy. However, limited studies focus on the contribution of stringency to sustainable energy. This study explores the contribution of environmental policy stringency and institutional quality on sustainable energy for the top 14 green economies by utilizing data from 1990 to 2022. In empirical analysis, the study applies the PMG-ARDL and CS-ARDL models to obtain the short- and long-run estimates. The study's findings indicate that after controlling the impact of technological innovation, foreign direct investment, population, economic globalization, and gross domestic product per capita environmental policy stringency and institutional quality significantly promote sustainable energy in the long run. Based on the results, the study recommends strictness in implementing policies is more critical than just designing environmental policies.